The Vertical Propagation of Inertial Waves in the Ocean. - Leaman,Kevin Douglas (1975)
A set of vertical profiles of horizontal ocean currents, obtained by electro-magnetic profilers in the Atlantic Ocean southwest of Bermuda in the spring of 1973, has been analyzed in order to study the vertical structure and temporal behavior of internal waves, particularly those with periods near the local inertial period. Doctoral thesis.